Highly selective and recyclable lanthanoids coordination polymers fluorescent sensors for 1-Hydroxypyrene. (1st January 2023) - Wang, Guangtu; Duan, Shaolong; Chen, Zhengcheng; Zeng, Yu; Wang, Ziyuan; Zou, Ping
Graphical abstract: Our group synthesized a series of coordination polymers, which is a novel fluorescence sensor for detecting trace amounts of 1-Hydroxypyrene. Abstract: Based on trivalent lanthanides, fumaric acid (H2 F) and 4-(pyridyl- N -oxide) methylphosphonic acid (H2 L), a new series of coordination polymers (the CP), namely, [Ln(HL)(F)(H2 O)]n (Ln = La( 1 ), Ce( 2 ), Pr( 3 ), Nd( 4 ), Sm( 5 ), Eu( 6 ), Gd( 7 )) were obtained under hydrothermal condition. Data for the prepared CPs was collected using single-crystal X-ray diffraction (SXRD), powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA) and luminescence spectra. The results show that, on the hand, complexes 1–7 are isomorphic, having 2D layered structures. On the other hand, the Eu 3+ ion content greatly affects the luminescence characteristic of complex 6, which is a novel fluorescence sensor for detecting trace amounts of 1-Hydroxypyrene (1-HP), with excellent sensitivity and high selectivity. For the fluorescent determination of 1-HP, complex 6 shows a linear response range of 0–100 µM, with an ultralow detection limit (LOD) of 2.76 μM. The fluorescence quenching mechanism of complex 6 by 1-HP may be result from spectral overlap and energy absorption competition.